HISTORY OF THE ORIGIN OF PROVERBS - Xaydarova Go'zalxon Xamdamjon qizi (Journal Park Publishing, 2022)
This article provides information about the history of the origin of proverbs, their place among the Uzbek people, what language they are derived from, what they mean, the size of proverbs, differences between proverbs (lyric, epic).
Keywords: proverb; lyric; folk